Analisis Yuridis Penerapan Pasal 3 Undang – Undang Nomor 8 Tahun 2010 : (Studi Kasus Tindak Pidana Pencucian Uang dari Hasil Tindak Pidana Narkotika pada Putusan Perkara Nomor 438/Pid.Sus/2014/PN Stb) - Ramadhan, Fachry; Yusuf, Hudi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Money laundering offenses, especially those related to narcotics, have garnered serious attention in Indonesia's legal system. This article provides an overview of the legal aspects of money laundering associated with narcotics crimes, focusing on the case of the defendant, Mohd. Azwar. The research employs a case study method and legal analysis to uncover the relationship between narcotics offenses and money laundering committed by the defendant. The results indicate that the defendant engaged in a series of financial transactions inconsistent with his income as a seafood trader, indicating money laundering from narcotics-related crimes. Although the defendant received a one-year prison sentence, the author argues that the sentencing should reflect the concept of Concursus or concurrency offenses, in line with Article 3 of Law Number 8 of 2010. In conclusion, there is a need for fair law enforcement and a broader understanding of the concept of concurrency in responding to money laundering offenses related to narcotics.